Formulation of Azithromycin Suspension as an Oral Dosage Form - H. Jaber, Saba; T.Salih, Zainab; M. Salmo, Hiba (Iraqi Journal of Pharmaceutical Sciences, 2017)
Azithromycin is the drug of choice in the treatment of several bacterial infections, most often those causing middle ear infection, bronchitis, pneumonia, typhoid and sinusitis. It’s also effective against certain urinary tract infections and venereal diseases. This study was carried out to prepare an acceptable suspension either as dry physical mixture powder or granules to be reconstituted, through studying the effect of various type and concentration of suspending agent (xanthan gum, hydroxypropyl methylcellulose (HPMC), either alone or in combination) on the release profile of the drug. The best prepared suspension formulas (H& III) were selected depending on the dissolution profile of each formulas and then compared with the reference suspensions (Zithromax and Azi-once).The viscosity, sedimentation volume, Resuspendability and expiration date were evaluated for the chosen formulas (H&III) and compared with references ZithromaxÒ and Azi-onceÒ.The result indicated that the chosen formula – H had better dissolution rate compared with references suspensions, Also it was less viscous than them.While other chosen formula – III had lower dissolution rate compared with ZithromaxÒ and higher dissolution rate than AZi – once, also it was less viscous than both references.It was found that the dry physically mixed powder (formula – H) was more stable than the granular suspension (Formula III) since the expiration date for formula H and formula III were 3.24 and 2.7 years respectively. Key words: Azithromycin, suspending agent, suspension.